Hubris, rapid capacity expansions and the competition in de novo ventures - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2010)
This study develops and tests the hubris theory of entrepreneurship as a means to explain the variation in failure rates amongst de novo ventures, complementing escalation and other behavioral explanations. It uses rapid increases in production capacity as a proxy for overconfidence, and firm failure to demonstrate hubris. In contrast to previous studies, we reason that overconfidence is more likely in situations where there is no dominant arch competitor for the focal de novo venture (i.e., low arch incumbency). Using data from the European passenger airline industry, we find empirical support that that overconfidence provides an adequate explanation for rapid increases in production capacity in de novo ventures, which in turn, provides a mediating (suppressing) pathway linking arch incumbency to firm failure.